Pengaruh Motivasi Berprestasi Dan Pengembangan Karier Terhadap Kinerja Guru Dengan Komitmen Organisasi Sebagai Variabel Mediasi Pada Sekolah Dasar Di Satuan Koordinasi Pendidikan Kecamatan Mlonggo Kabupaten Jepara (International Forum of Researchers and Lecturers, 2023)
This research on teacher performance aims to analyze the effect of achievement motivation and career development on teacher performance with organizational commitment as a mediating variable. The population in this study were all public elementary school teachers in the Education Coordination Unit, Mlonggo District, Jepara Regency, amounting to 298 people. Determination of the number of samples in this study based on Isaac's table and with an error rate of 5%, obtained 158, and the data processed were 125. The method of analysis used path analysis with multiple regression models. The results of hypothesis testing show that achievement motivation has a positive and significant effect on organizational commitment, so it can be interpreted that the higher the achievement motivation, the higher the organizational commitment. Career development has a positive and significant effect on organizational commitment, so it can be interpreted that the better the career development, the higher the organizational commitment. Organizational commitment has a positive and significant effect on teacher performance, so it can be interpreted that the higher the organizational commitment, the better the teacher's performance. Achievement motivation has a positive and significant effect on teacher performance, so it can be interpreted that the higher the achievement motivation, the better the teacher's performance. Career development has a positive and significant effect on teacher performance so that it can be interpreted that the better the career development carried out, the better the teacher's performance. The results of the analysis of mediating variables using the Sobel test, found that organizational commitment can mediate the effect of achievement motivation on teacher performance. This proves that organizational commitment as a mediating variable of the influence of achievement motivation on teacher performance. Organizational commitment can mediate the effect of career development on teacher performance. This proves that organizational commitment as a mediating variable of the influence of career development on teacher performance.